Efeito da terapia com Laser de Baixa Intensidade (LBI) em modelo experimental de inflamação alérgica pulmonar induzida por House Dust Mite (HDM) - estudo de dosimetria - Oliveira, Nicole Cristine Rigonato de (2018)
Asthma is characterized by chronic inflammation in the airways. It presents high prevalence, economic and social cost. Several models have been proposed aiming the discovery of new therapies. Low Level Laser Therapy (LLLT) is relatively new and effective, of very low cost, with no side effects. As for laser therapy, there is still no consensus on the optimal dose to be used. In this sense, the objective of the present study was to evaluate the effect of LLLT with different energies on chronic lung inflammation in an experimental model of asthma induced by House Dust Mite (HDM). We used Balb/c mice, divided into 10 groups: Basal, HDM, Laser (1J, 3J, 5J and 7,5J) and HDM+Laser (1J, 3J, 5J and 7,5J). The LLLT used was diode (660 nm, 100 mW) and for each energy, we used different times (10s, 30s, 50s and 75s) in three points: trachea, left lobe and right. For the experimental model, the animals received orotracheal administration of 100ug/animal HDM on days 0, 14, followed by 3 weekly administrations by day 56. After 24 hours, we studied functional and structural parameters, such as pulmonary inflammation through bronchoalveolar lavage fluid (BALF), total and differential cell count, quantification of CD11b, LY6G, Syglec F, CD3+, CD4+ and CD8+ in the lung, the percentage of 7AAD and ANEXINA V, as well as CD4+, STAT6+, GATA3+ and IL-4+ lymphocytes in BALF by flow cytometry, cytokines in BALF and pulmonary homogenate (IL-4, IL-5, IL-10 and IL-13) by ELISA, morphometric analysis of eosinophilic peribronchial infiltrate (LUNA), mucus (PAS), collagen (PSR), bronchoconstriction index, bronchial and muscular thickening (HE), pulmonary mechanics (pulmonary elastance) and pulmonary reactivity by the Power Lab method. Results showed that LLLT was able to modulate observed pulmonary inflammation by reducing the number of cells in the BALF, as well as reducing the percentage of neutrophils, eosinophils and T lymphocytes (CD4+ and CD8+). In addition, it decreased CD4+ STAT6+ and GATA3+ lymphocytes, as well as apoptosis and cell necrosis. On the other hand, laser therapy increased the percentage of macrophages and IL-10 and reduced levels of IL-4, IL-5 and IL-13 in the BALF and pulmonary homogenate. LLLT was able to reduce mucus production. Regarding the structural alterations, we observed a significant reduction in the quantification of peribronchial eosinophils, collagen deposition, bronchoconstriction index, bronchial and muscular 9 thickening in the airways, after LLLT treatment. Finally, in functional analysis, the evaluation of tracheal reactivity to methacholine and evaluation of pulmonary mechanics presented a decrease in all groups submitted to laser therapy. We conclude that the use of laser therapy in the treatment of chronic inflammation of the airways attenuated the inflammatory process, functional parameters and pulmonary structure. We emphasize in general that the 3J laser presented better results. Thus, photobiomodulation can be considered a promising tool for the treatment of chronic pulmonary allergic inflammation observed in asthma.